Disk transport rates from Ti isotopic signatures of refractory inclusions. (10th November 2022) - Render, Jan; Bryson, James F. J.; Ebert, Samuel; Brennecka, Gregory A.
Abstract: The early solar system was a dynamic period during which the formation of early solids set into motion the process of planet building. Although both astrophysical observations and theoretical modeling demonstrate the presence of widespread transport of material, we lack concrete quantitative constraints on timings, distances, and mechanisms thereof. To trace these transport processes, one needs objects of known early formation times and these objects would need to be distributed throughout parent bodies with known accretion times and distances. Generally, these criteria are met by "regular" (i.e., non–fractionated and unidentified nuclear and excluding hibonite‐rich) Ca‐Al‐rich inclusions (CAIs) as these objects formed very early and close to the young Sun and contain distinctive nucleosynthetic isotope anomalies that permit provenance tracing. However, nucleosynthetic isotopic signatures of such refractory inclusions have so far primarily been analyzed in chondritic meteorites that formed within 4 AU from the Sun. Here, we investigate Ti isotopic signatures of four refractory inclusions from the ungrouped carbonaceous chondrite WIS 91600 that was previously suggested to have formed beyond 10 AU from the Sun. We show that these inclusions exhibit correlated excesses in 50 Ti and 46 Ti and lack large Ti isotopic anomalies that would otherwise be indicative of more enigmatic refractory materials with unknown formation ages. Instead, these isotope systematics suggest the inclusions to be genetically related to regular CAIs commonly found in other chondrites that have a broadly known formation region and age. Collectively, this implies that a common population of CAIs was distributed over the inner 10 AU within 3.5 Myr, yielding an average (minimum) speed for the transport of millimeter‐scale material in the early solar system of 1 cm s −1 .